Pre-critical fluctuations and what they disclose about heterogeneous crystal nucleation. Issue 1 (December 2017) - Fitzner, Martin; Sosso, Gabriele; Pietrucci, Fabio; Pipolo, Silvio; Michaelides, Angelos
Abstract Heterogeneous crystal nucleation is ubiquitous in nature and at the heart of many industrial applications. At the molecular scale, however, major gaps in understanding this phenomenon persist. Here we investigate through molecular dynamics simulations how the formation of precritical crystalline clusters is connected to the kinetics of nucleation. Considering heterogeneous water freezing as a prototypical scenario of practical relevance, we find that precritical fluctuations connote which crystalline polymorph will form. The emergence of metastable phases can thus be promoted by templating crystal faces characteristic of specific polymorphs. As a consequence, heterogeneous classical nucleation theory cannot describe our simulation results, because the different substrates lead to the formation of different ice polytypes. We discuss how the issue of polymorphism needs to be incorporated into analysis and comparison of heterogeneous and homogeneous nucleation. Our results will help to interpret and analyze the growing number of experiments and simulations dealing with crystal polymorph selection. Heterogeneous nucleation is a process that mediates the birth of many crystalline materials, but is not fully understood. Here, the authors show that the study of precritical cluster fluctuations paves new ways for the identification of polymorphism, polymorphic control and theoretical modeling.